Management of presacral tumors: Our experience with posterior approach. (2015) - Saxena, Dhananjay; Pandey, Abhinav; Bugalia, Rajendra Prasad; Kumar, Mahendra; Kadam, Raju; Agarwal, Vipul; Goyal, Amit; Kankaria, Jeevan; Jenaw, Raj Kamal
Highlights: Presacral tumors are rare variety of space occupying lesions which due to their location, etiological heterogeneity and difficult surgical approach, present a challenge to treating physician. Surgical excision remains the treatment of choice for presacral masses. Posterior surgical approach, if applied judicially, in carefully selected cases, remains an attractive option as it provides better surgical exposure, is more direct approach, commodious to adopt, easy to learn with quicker post-operative recovery. Abstract: Introduction: Presacral tumors are a rare variety of space occupying lesions arising in the presacral space. Most of the tumors are congenital in origin. Due to obscure anatomic location, difficult surgical approach and etiological heterogeneity, tumors arising here pose a diagnostic and therapeutic challenge. We report our experience of 10 cases of presacral tumors with posterior approach being used in 6. Materials and methods: A retrospective analysis was conducted on 10 cases of presacral tumors managed at our hospital during a period of 14 months (May 2013–July 2014). 9 cases were operated while one had advanced disease and was referred for palliative care. Complete en bloc excision of the mass was possible in 8 cases. Finally, presenting complaints, clinical diagnosis, surgical procedure and histopahological findings of the cases were studied. Results: All of our patients were females in the age group of 18–50 (mean 28.4) years. The pathological findings included schwannoma, leiomyosarcoma, hemangiopericytoma, neurofibroma, paraganglioma and rest were developmental cysts. 6 cases were managed using the posterior approach and rest by anterior approach. There was no major complication or mortality in the follow up. Conclusion: Complete surgical excision remains the mainstay of therapy. Surgical approach depends upon the location, size, local invasion and surgical expertise of the surgeon. Benign tumors have a good prognosis while the prognosis in malignant tumors remains guarded due to difficulty in obtaining safe resection margins. Posterior approach is an attractive option for low lying, benign tumors that is more direct, with better exposure and quicker recovery.